2017
DOI: 10.1073/pnas.1707453114
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of water reorientational slowing down in concentrated ionic solutions

Abstract: Water dynamics in concentrated ionic solutions plays an important role in a number of material and energy conversion processes such as the charge transfer at the electrolyte-electrode interface in aqueous rechargeable ion batteries. One long-standing puzzle is that all electrolytes, regardless of their "structure-making/breaking" nature, make water rotate slower at high concentrations. To understand this effect, we present a theoretical simulation study of the reorientational motion of water molecules in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
74
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(82 citation statements)
references
References 38 publications
6
74
2
Order By: Relevance
“…These experimental results therefore strongly differ from the conclusions of a previous study on sodium and potassium thiocyanate. 12 It was suggested that the increase in viscosity was the main reason for retarded dynamics at high concentrations, a conclusion that was meant to be general for all ion solutions. 12 In contrast, the above-described experimental results support the conclusions of our prior study, 7 where we suggested that the increased viscosity becomes important at high concentration for some specific salts such as sodium perchlorate, but that this does not apply to many other salts where viscosity has a minor effect on water dynamics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These experimental results therefore strongly differ from the conclusions of a previous study on sodium and potassium thiocyanate. 12 It was suggested that the increase in viscosity was the main reason for retarded dynamics at high concentrations, a conclusion that was meant to be general for all ion solutions. 12 In contrast, the above-described experimental results support the conclusions of our prior study, 7 where we suggested that the increased viscosity becomes important at high concentration for some specific salts such as sodium perchlorate, but that this does not apply to many other salts where viscosity has a minor effect on water dynamics.…”
Section: Resultsmentioning
confidence: 99%
“…M), which are likely due to limitations of this simplified description, and do not necessarily affect the applicability of the jump model, in contrast to what was implied in ref 12. …”
mentioning
confidence: 77%
See 1 more Smart Citation
“…This same argument, however, can be used to reason that the general deceleration does not entirely come from the retarded jump either, since the decelerations in many concentrated electrolytes are larger than Our point in ref. 5, instead, is that at higher concentrations the ions can have nonnegligible effects on both jump and frame components. However, the effect on the jump component can be either acceleration or deceleration (e.g., figure 4 in ref.…”
mentioning
confidence: 99%
“…Stirnemann et al (1) claim that the high-concentration regime (>5 M) studied in ref. 5 is not relevant for aqueous batteries or for biological processes. A recent paper (7), however, reported using the aqueous electrolytes up to 21 M in lithium-ion batteries, which enables high-voltage aqueous lithium-ion chemistries.…”
mentioning
confidence: 99%